FAKTOR-FAKTOR PENDUKUNG PENGGUNAAN ANTREAN ONLINE DALAM MENUNJANG PENINGKATAN MUTU LAYANAN BAGI BPJS KESEHATAN KEDEPUTIAN WILAYAH XI - Sinungan, Nuke Paulin; Sri Darma, Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.11.TAHUN.2023DO - 10.24843/EEB.2023.v12.i11.p13, 2023)
The aim of this research is to analyze the influencing factors for increasing the use of online queues to support improving the quality of service for BPJS Health Deputy Region The population of the research carried out was all JKN BPJS Health participants who accessed the Mobile JKN application in the Bali Nusra region, totaling 43,838 people. From calculations using the Slovin formula, the sample of respondents in this study amounted to 100 respondents. There is a significant positive influence of performance expectancy, effort expectancy and social influence on behavioral intention to use the JKN BPJS Health Online queuing system with the Mobile JKN application. There is a significant positive influence of Facilitating Conditions on behavioral intention to use the JKN BPJS Health Online queuing system with the Mobile JKN application. There is a significant negative influence of technology anxiety on behavioral intention to use the JKN BPJS Health Online queuing system with the Mobile JKN application. There is a significant positive influence of behavioral intention on use behavior for using the JKN BPJS Health Online queuing system with the Mobile JKN application.